Reactive magnetron plasma modification of electrospun PLLA scaffolds with incorporated chloramphenicol for controlled drug release - Rakina, Apollinariya A.; Fedorishin, Dmitry A.; Khvastunova, Arina O.; Spiridonova, Tatiana I.; Kozelskaya, Anna I.; Kzhyshkowska, Julia; Tverdokhlebov, Sergei I.; Kurzina, Irina (Polymers, 2022)
Surface modification with the plasma of the direct current reactive magnetron sputtering has demonstrated its efficacy as a tool for enhancing the biocompatibility of polymeric electrospun scaffolds. Improvement of the surface wettability of materials with water, as well as the formation of active chemical bonds in the near-surface layers, are the main reasons for the described effect. These surface effects are also known to increase the release rate of drugs incorporated in fibers. Herein, we investigated the effect of plasma modification on the chloramphenicol release from electrospun poly (lactic acid) fibrous scaffolds. Scaffolds with high—50 wt./wt.%—drug content were obtained. It was shown that plasma modification leads to an increase in the drug release rate and drug diffusion coefficient, while not deteriorating surface morphology and mechanical properties of scaffolds. The materials’ antibacterial activity was observed to increase in the first day of the experiment, while remaining on the same level as the unmodified group during the next six days. The proposed technique for modifying the surface of scaffolds will be useful for obtaining drug delivery systems with controlled accelerated release, which can expand the possibilities of local applications of antibiotics and other drugs.
Gesehen am 28.05.2024